10 Ways to waste time on the Web. - Arar, Yardena (PC World Philippines)
Want to idle away a few minutes--or hours? These sites will help you name that tune, test your knowledge of hurricanes, launch a hedgehog, or write a haiku. You'll wonder where the time went.